Utility of echocardiography in patients with suspected acute myocardial infarction in the presence of left bundle-branch block. (25th November 2020) - Ratmann, P.D; Nestelberger, T; Cullen, L; Lindahl, B; Boeddinghaus, J; Rubini, M; Lopez Ayala, P; Than, M; Greenslade, J; Mueller, C
Abstract: Background: Rapid identification of acute myocardial infarction (AMI) as life-threatening disorder by clinical assessment, cardiac troponin and the electrocardiogram (ECG) is important for the early initiation of highly effective, evidence-based therapy. Patients presenting with suspected AMI and left bundle branch block (LBBB) to the emergency department (ED) represent a unique diagnostic and therapeutic challenge, as altered ventricular depolarization masks changes in ventricular repolarization associated with myocardial ischemia. Current guidelines suggest, based on expert opinion, early echocardiography as a helpful tool in patients with suspected AMI and LBBB to identify new wall motion abnormalities, which guides further diagnostics strategies in these patients. Purpose: To evaluate the diagnostic accuracy of echocardiography among patients with suspected AMI and LBBB in the recorded ECG at ED presentation. Methods: We prospectively evaluated the diagnostic accuracy of echocardiography in patients with LBBB presenting with chest discomfort to 26 ED's in three international, prospective, diagnostic studies. Two independent cardiologists centrally adjudicated the final diagnosis in each study according to the universal definition of myocardial infarction. All patients underwent a clinical assessment that included standardized and detailed medical history including assessment of chest pain characteristics, vital signs, physical examination, 12-lead ECG, continuous ECG rhythm monitoring, pulse oximetry, standard blood test, and chest radiography and echocardiography if indicated. We compared echocardiographic findings in patients with LBBB who were diagnosed with an AMI to those without an AMI. Results: Among 283 patients presenting with chest pain and LBBB to the ED, AMI was the final diagnosis in 36% (102 of 283 patients) of patients. An echocardiography had been performed in 100/283 patients (35%) in the emergency department. AMI was the final diagnosis in 41/100 (41%) of patients. A wall motion abnormality in any region was seen in 77 (77%) of patients with no difference between patients diagnosed with AMI (33 patients, 81%) versus without AMI (44 patients, 75%, p=0.49). Additionally, we found no differences for each wall region (Table 1). Most patients with LBBB had moderately reduced left ventricular ejection fraction (LVEF, median 40%), a dilated left atrium (67%) or left ventricular hypertrophy (55%) without any differences between the two groups (Table 1). Conclusions: Early echocardiography in patients with suspected AMI and LBBB provided only limited utility to identify patients, which may benefit from immediate coronary angiography. Our findings scrutinize current guidelines and downgrades the utility of echocardiography in this setting. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Swiss National Science Foundation, the Swiss Heart Foundation, the European Union, the Cardiovascular Research Foundation Basel, the University Hospital Basel, Queensland Emergency Medicine Research Foundation, Christchurch Heart Institute and Health Research Council and Heart Foundation of New Zealand, Christchurch Emergency Care Foundation